Monitoring surface resonances on Co2MnSi(100) by spin-resolved photoelectron spectroscopy - Braun, J.; Jourdan, Martin; Kronenberg, A.; Chadov, S.; Balke, Benjamin; Kolbe, M.; Gloskovskii, A.; Elmers, H. J.; Schoenhense, Gerd; Felser, Claudia; Klaeui, M.; Ebert, H.; et al. (Physical Review B - Condensed Matter and Materials Physics, 2015)
The magnitude of the spin polarization at the Fermi level of ferromagnetic materials at room temperature is a key property for spintronics. Investigating the Heusler compound Co2MnSi, a value of 93% for the spin polarization has been observed at room temperature, where the high spin polarization is related to a stable surface resonance in the majority band extending deep into the bulk. In particular, we identified in our spectroscopical analysis that this surface resonance is embedded in the bulk continuum with a strong coupling to the majority bulk states. The resonance behaves very bulklike, as it extends over the first six atomic layers of the corresponding (001) surface. Our study includes experimental investigations, where the bulk electronic structure as well as surface-related features have been investigated using spin-resolved photoelectron spectroscopy (SR-UPS) and for a larger probing depth spin-integrated high energy x-ray photoemission spectroscopy (HAXPES). The results are interpreted in comparison with first-principles band structure and photoemission calculations which consider all relativistic, surface, and high-energy effects properly.
CRIS-Team Scopus Importer:2023-03-20